How to Use Imaging in Clinical Practice - Vinall, Phil (MD Conference Express, 2006)
Conventional radiography has long been used to track changes and diagnose rheumatoid arthritis (RA), ankylosing spondylitis, and osteoarthritis. Though still valuable, conventional radiography cannot detect soft tissue changes or early RA bone damage. Magnetic resonance imaging (MRI) and ultrasonography (US) allow direct visualization of early inflammatory changes in the joint. MRI measurements/scores for erosion, bone edema, and synovitis have been developed for the hand, wrist, and foot.